Investigation of the Performance of the Ecofriendly Fiber-Reinforced Asphalt Mixture as a Sustainable Pavement Material - Bowen Guan; Jianan Liu; Jiayu Wu; Jingyi Liu; Haitao Tian; Tengbin Huang; Chengcheng Liu; Tao Ren (Advances in Materials Science and Engineering)
This article presents a study to evaluate the performance of the ecofriendly calcium sulfate whisker fiber- (CSWF-) reinforced asphalt mixture as a sustainable pavement material. Asphalt mixtures containing 0.2 wt.%, 0.4 wt.%, 0.6 wt.%, and 0.8 wt.% of the CSWF were designed by the Marshall method. Asphalt mixtures without fiber were also prepared as control samples. The Marshall test, wheel-tracking test, low-temperature bending test, water sensitivity test, and fatigue test were conducted to evaluate the performance of the CSWF asphalt mixture. And the mechanism of fiber reinforcement was discussed. The results showed that the CSWF could improve the high-temperature stability and low-temperature crack resistance of the asphalt mixture. Water stability of asphalt mixtures in the presence of the CSWF was also improved. When the CSWF content was 0.4 wt.% of the total mixture, the performance of the asphalt mixture is the best. Compared with the conventional asphalt mixture, the CSWF asphalt mixture not only utilized power plant waste effectively to preserve ecosystems but also improved the performance of the pavement, which is suggested to be used in sustainable pavement construction and rehabilitation.